Vehicle stability enhancement and rollover prevention by a nonlinear predictive control method - Arslan, M. Selcuk; Sever, Mert (SAGE PUBLICATIONS LTD, 2019)
In this study, a nonlinear predictive control method is developed for the active steering control of a sport utility vehicle. The method is tested on a nonlinear mathematical model of an 11-degree-of-freedom vehicle. The system performance is evaluated by considering that the control law must keep the actual yaw rate close to the desired yaw rate and minimizing the vertical load changes at each wheel. The latter is proposed for this work. The vertical load changes play an important role in the dynamics and the stability of the system. The effectiveness of the control method is demonstrated through numerical simulation by using a vehicle model that includes three case studies: rapid lane change at low and high velocities and the fishhook manoeuvre. The results show that the stability of the vehicle is maintained and its rollover propensity is decreased. In addition, the proposed controller is compared with a well-known linear model predictive controller.
Keywords: Active steering control; predictive control; rollover prevention; active safety; vehicle dynamics; ACTIVE STEERING SYSTEMS; INTEGRATED CONTROL; YAW STABILITY; DESIGN; Automation & Control Systems; Instruments & Instrumentation